1999
DOI: 10.1086/307862
|View full text |Cite
|
Sign up to set email alerts
|

Pulsar Magnetospheric Emission Mapping: Images and Implications of Polar Cap Weather

Abstract: The beautiful sequences of "drifting" subpulses observed in some radio pulsars have been regarded as among the most salient and potentially instructive characteristics of their emission, not least because they have appeared to represent a system of subbeams in motion within the emission zone of the star. Numerous studies of these "drift" sequences have been published, and a model of their generation and motion articulated long ago by Ruderman & Sutherland (1975); but efforts thus far have failed to establish a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
211
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(234 citation statements)
references
References 22 publications
(27 reference statements)
22
211
1
Order By: Relevance
“…In the model, radio emission is the result of the secondary particles scattering o † "" low-frequency waves.ÏÏ The waves are assumed to be produced by either the breaking down of the vacuum polar gap or other sorts of short time oscillations or microinstabilities 1996). The gap sparking may exist (Bjornsson above the polar cap, as shown by new observations by Deshpande & Rankin (1999) and by Vivekanand & Joshi (1999). If so, there must be low-frequency waves emitted by such sparking.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the model, radio emission is the result of the secondary particles scattering o † "" low-frequency waves.ÏÏ The waves are assumed to be produced by either the breaking down of the vacuum polar gap or other sorts of short time oscillations or microinstabilities 1996). The gap sparking may exist (Bjornsson above the polar cap, as shown by new observations by Deshpande & Rankin (1999) and by Vivekanand & Joshi (1999). If so, there must be low-frequency waves emitted by such sparking.…”
Section: Introductionmentioning
confidence: 93%
“…The radius of a sparking spot was assumed to have the same scale as the inner gap height (Gil 1998), which Deshpande & Rankin (1999) estimated to be about 10 m. We took this value in the following simulations, but we have found that changing this dimensional size does not a †ect our results. We also assumed that the number density of particles in a bunch n e has a maximum in the center and declines toward the edge.…”
Section: T Ransient Beam From a Bunch Of Particles : Simulationmentioning
confidence: 99%
“…Another complication is that a pulse is often composed of several identiÐable components, some of which can be polarized in the orthogonal mode (a result of propagation e †ects in the magnetosphere) obscuring the "" true ÏÏ polarization. Furthermore, the pulse itself might not even contain an identiÐable core component, being composed instead of emission from random patches within a cone (e.g., Lyne & Manchester 1988 ;Manchester 1995 ;Deshpande & Rankin 1999). Accordingly, measurements of are rarely attempted, ( 0 measurements of a are rarely trusted, and measurements of f are rarely questioned.…”
Section: Fig 8è(a)mentioning
confidence: 99%
“…Deshpande & Rankin (1999) demonstrated clearly that the non-corotating subbeams associated with drifting subpulses actually lag the stellar rotation. This finding strenghtens the VG plasma E × B drift hypothesis.…”
Section: Introductionmentioning
confidence: 95%